Antibacterial activities of medicinal plants used in Mexican traditional medicine. (17th August 2017) - Sharma, Ashutosh; Flores-Vallejo, Rosario del Carmen; Cardoso-Taketa, Alexandre; Villarreal, María Luisa
Abstract: Ethnopharmacological relevance: We provide an extensive summary of the in vitro antibacterial properties of medicinal plants popularly used in Mexico to treat infections, and we discuss the ethnomedical information that has been published for these species. Materials and methods: We carried out a bibliographic investigation by analyzing local and international peer-reviewed papers selected by consulting internationally accepted scientific databases from 1995 to 2014. We provide specific information about the evaluated plant parts, the type of extracts, the tested bacterial strains, and the inhibitory concentrations for each one of the species. We recorded the ethnomedical information for the active species, as well as their popular names and local distribution. Information about the plant compounds that has been identified is included in the manuscript. This review also incorporates an extensive summary of the available toxicological reports on the recorded species, as well as the worldwide registries of plant patents used for treating bacterial infections. In addition, we provide a list with the top plant species with antibacterial activities in this review Results: We documented the in vitro antibacterial activities of 343 plant species pertaining to 92 botanical families against 72 bacterial species, focusing particularly on Staphylococcus aureus, Mycobacterium tuberculosis, Escherichia coli and Pseudomonas aeruginosa . The plant families Asteraceae, Fabaceae, Lamiaceae and Euphorbiaceae included the largest number of active species. Information related to popular uses reveals that the majority of the plants, in addition to treating infections, are used to treat other conditions. The distribution of Mexican plants extended from those that were reported to grow in just one state to those that grow in all 32 Mexican states. From 75 plant species, 225 compounds were identified. Out of the total plant species, only 140 (40.57%) had at least one report about their toxic effects. From 1994 to July 2014 a total of 11, 836 worldwide antibacterial patents prepared from different sources were recorded; only 36 antibacterial patents from plants were registered over the same time period. We offered some insights on the most important findings regarding the antibacterial effects, current state of the art, and research perspectives of top plant species with antibacterial activities in vitro . Conclusions: Studies of the antibacterial in vitro activity of medicinal plants popularly used in Mexico to treat infections indicate that both the selection of plant material and the investigation methodologies vary. Standardized experimental procedures as well as in vivo pharmacokinetic studies to document the effectiveness of plant extracts and compounds are necessary. This review presents extensive information about the medicinal plants possessing antibacterial activity that has been scientifically studied and are popularly used in Mexico. We anticipate that this review will be of use for future studies because it constitutes a valuable information tool for selecting the most significant plants and their potential antibacterial properties. Graphical abstract: